EFFECTS OF DIFFERENT SHADING PERIODS ON THE INITIAL GROWTH OF Cariniana estrellensis (Raddi) Kuntze - Almeida, Rodolfo Soares de; Baroni, Gabriel de Resende; Nieri, Erick Martins; Melo, Lucas Amaral de (Floresta, 2022)
A better understanding of the production cycle and best methods for cultivating the seedlings of native Brazilian species are needed to further develop ecological restoration projects and close the knowledge gap on native species. This work aimed to evaluate the effects of different shading periods on the production of nursery seedlings of Cariniana estrellensis. The shade periods were based on the number of days under 50% shade (0, 30, 60, 90, 120, 150, and 180 days of experiment), using a completely randomized design, with four replicates, and 25 seedlings per parcel. We measured the height, diameter, biomass of the shoot and roots, number of leaves, and quality of seedlings, using the Dickson quality index assessment. We found a positive and linear relationship between all variables and the shading period, with a prolonged period in shade providing the best results. We concluded that Cariniana estrellensis seedlings grow more efficiently in shade.